Relationship Between Body Mass Index and Survival Among Critically Ill Patients With Cirrhosis. (June 2022) - Choi, Chansong; Lennon, Ryan J.; Choi, Dae Hee; Serafim, Laura Piccolo; Allen, Alina M.; Kamath, Patrick S.; Shah, Vijay H.; de Moraes, Alice Gallo; Simonetto, Douglas A.
Background: Obesity paradox is a phenomenon in which obesity increases the risk of obesity-related chronic diseases but paradoxically is associated with improved survival among obese patients with these diagnoses. Objectives: The aim of this study was to explore the obesity paradox among critically ill patients with cirrhosis admitted to the Intensive Care Unit. Methods: A retrospective cohort of 1, 143 consecutive patients with cirrhosis admitted to the ICU between January of 2006 and December of 2015 was analyzed. Primary outcome of interest was in-hospital mortality with secondary end points including ICU and short-term mortality at 30 days post ICU admission. Results: Logistic regression with generalized additive models was used, controlling for clinically relevant and statistically significant factors to determine the adjusted relationship between body mass index (BMI) and ICU, post-ICU in-hospital, and 30 day mortality following ICU discharge. ICU and hospital length of stay was similar across all BMI classes. Adjusted ICU mortality was also similar when stratified by BMI. However, a significant reduction in post-ICU hospital mortality was observed in class I and II obese patients with cirrhosis (BMI 30-39.9 kg/m 2 ) compared to normal BMI (OR = 0.41; 95% CI, 0.20 to 0.83; P = 0.014). Similarly, overweight (BMI 25-29.9 kg/m 2 ) and class I and II obese patients with cirrhosis had significantly lower 30-day mortality following ICU discharge (OR = 0.52, 95% CI 0.31 to 0.87; P = 0.014; OR = 0.50, 95% CI 0.29 to 0.86; P = 0.012, respectively) compared to those with normal BMI. Conclusion: The signal of obesity paradox is suggested among critically ill patients with cirrhosis.